Synthesis and Studies of Novel Optically Active Schiff’s Base Derivatives and their Antimicrobial Activities - Ishwar J. Patel; Shailesh J. Parmar (E-Journal of Chemistry)
Several new Schiff’s base derivatives were prepared by condensing various substituted benzaldehyde with 1-(4-aminophenyl)-2-{4-[(S)-(4-chlorophenyl)(phenyl) methyl]-1-piperazinyl}ethanone in presence of acid catalyst under reflux condition. All the compounds were characterized by elemental analysis and spectral studies. The newly synthesized compounds were evaluated for their antibacterial and antifungal activity.